The Effect of PjBL Assisted by Mentimeter Media on Learning Outcomes of Geometry Material - I Putu Suardipa; Nyoman Lisna Handayani; I Komang Wahyu Wiguna; Made Ferry Kurniawan (International Journal of Elementary Education, 2025)
The low mathematics learning outcomes among elementary school students, particularly in the topic of decimal numbers, are caused by a lack of active student engagement, limited variation in teaching methods, and minimal integration of technology in the learning process. The aim of this study is to analyze the effectiveness of the Project-Based Learning (PjBL) model assisted by the digital media Mentimeter in improving elementary students' mathematics learning outcomes on the topic of decimal numbers. This research employed a quasi-experimental method with a pre-test post-test control group design, involving 186 fourth-grade elementary school students. The sample was selected through random sampling, with Class IV A as the experimental group (27 students) and Class IV B as the control group (15 students). Data were collected through observation, interviews, tests, and documentation. A t-test was used to analyze the data. The t-test results showed that among the 32 tested students, the tvalue was 7.074 and the ttable was 1.683, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (H1) was accepted, revealing a significant difference between the two groups. This study implies the importance of integrating project-based learning models with the support of interactive digital media such as Mentimeter to create a more engaging, participatory, and meaningful learning experience for elementary school students, especially in mathematics education.